Multivariate analysis of water quality parameters in Ogunpa river: human health implications - Akin-Oriola, G.; Tayo, B. (2000)
The study was aimed at assessing the quality status of water from the Ogunpa river and its implications on the health of inhabitants of the densely populated city of Ibadan in Nigeria. Pattern of changes in chemical parameters and trace metals was strongly influenced by season, with observed changes among such parameters as transparency, dissolved oxygen, iron, chromium and carbon dioxide. The habit of dumping refuse and faeces in the river has contributed to the high organic pollution of the river. The polluted river is unfortunately a source of drinking water to a section of the community of the city (due to the city's erratic water supply), and hence poses tremendous health hazard. A total of 34 phytoplankton species, most of which were pollution tolerant were recorded. Levels of zinc and manganese recorded (though not potentially hazardous) fur exceeded the World Health Organisation's recommended limits for drinking water. However more potentially dangerous was the identification of a blue, green algae, Oscillatoria spp., which produces anatoxin -an aIkaloid. Anatoxin is a post-synaptic neuromuscular blocking agent responsible for respiratory failure. The need for monitoring the chemical and other parameters of the river, and necessary education on health measures and hygiene are therefore essential.